Exposure to multiple mycotoxins in domestic and imported rice commercially traded in Tehran and possible risk to public health. (2021) - Eslamizad, Samira; Yazdanpanah, Hassan; Hadian, Zahra; Tsitsimpikou, Christina; Goumenou, Marina; Shojaee AliAbadi, Mohammad Hossein; Kamalabadi, Mahdie; Tsatsakis, Aristides
Graphical abstract: Highlights: The assessed Aflatoxin B1 intake for the adults and children through rice consumption exceeds the established safe levels. The mean and median HI for adults was below one, and mean HI for children was close to one. Cancer risk through consumption of domestic rice was higher than cancer risk due to consumption of imported rice. More focus on the reduction of mycotoxins contamination in rice seems to be necessary. Abstract: Mycotoxins are secondary fungi metabolites that induce acute and chronic toxic effects in humans and animals. In the present study, nine mycotoxins including aflatoxins (AFB1, AFB2, AFG1 and AFG2 ), fumonisins (FB1 and FB2 ), Ochratoxin A (OTA), deoxynivalenol (DON), and zearalenone (ZEN) were determined in one hundred rice samples collected from Tehran using high performance liquid chromatography (HPLC) with fluorescence or photodiode array detector. In addition, possible risk to public health was investigated by assessing dietary exposure through rice consumption, the margin of exposure (MOE), respective risk of cancer and hazard index (HI) of the monitored mycotoxins in children and adults. The higher mean levels were determined for DON (102.22 μg.Kg −1 ), followed by FB1 (85.00 μg.Kg −1 ). For the rests of mycotoxins the levels did not exceed 20 μg.Kg −1 . The estimated AFB1 intake for the adults and children through rice consumption exceeds the safe levels established for both carriers and non-carriers of hepatitis B virus. The mean and median determined exposure levels of OTA, DON ZEN and FB1, were found lower than the Provisional Maximum Tolerable Daily Intake (PMTDI) value for both adults and children of Tehran that consuming domestic and imported rice. The mean HI for adults and median HI for adults and children were below one, and mean HI for children was close to one. All the mean, median and maximum MoE values were <10, 000 in adults and children, indicating a risk due to AFB1 exposure through rice consumption in Tehran. In addition, the calculated mean cancer risk in adult and child populations of Tehran were 0.27 and 0.64 cases per year per 10 5 individuals, respectively, that shows population in Tehran could be at risk of cancer due to AFB1 exposure through rice consumption as calculated. So further studies are necessary for the monitoring mycotoxins in rice and different food products as well as estimating average dietary exposure and cumulative exposure assessment of mycotoxins for main foods in IR Iran.